(3GddeMI GdHOQjI aj GdOhdI GdfUQjIs - (3CHh YHO Gddg dSGf GdOjf eMeO Hf YHO Gddg Hf SYjO GHf GdNWjH GdZQfGWi GdCfOdSj,J (B776 (3g` s
(3ChdgG (B:s
(3CeGHYO, aEf af JGQjN GdRGFd YHQI dChdi Gdfgi, hPcQi def Zad Yf Gddg dPdc CLdjJ aj gPG GdcJGH PcQ edhc GdOhdI GdfUQjI Ydi fSb s
(3BNQgG (B:s
(3hbO Bf dfG Cf fNJe gPG GdSaQ hfbJUQ Ydjg, Edi Cf jSfj Gddg GdhLgI GdMLGRjI , afSJCfa JbjjOkG BNQ eJUdkG Hg aj PcQ eG fMd Hg ef GdCbWGQ, hfJdbGg ef GdCNHGQ Ef TGA Gddg s
(3GfXQ Qbe (B428 (3JGQjNs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B261 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B372 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B359 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs